PENGARUH RASIO PROFITABILITAS DAN RASIO LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PT. LIPPO KARAWACI TBK - RAHMAYANTI, ERY; RIMAWAN, M.; HUDA, NURUL (Universitas Mahasaraswati K. Mataram, 2024)
The objective of this study is to assess the impact of the profitability ratio and liquidity ratio on the valuation of PT. Lippo Karawaci Tbk. The balance statement comprises Current Assets, Current Liabilities, Total Equity, Inventory, and Profit and Loss represented by Net Profit after Tax for a span of 12 years, from 2011 to 2022. Purposive sampling is a research strategy that involves selecting participants based on specific criteria. Linear regression is a statistical analytic approach used to assess hypotheses, starting with the basic assumption test. The test results indicate that the profitability ratio, as quantified by Return on Equity (ROE), does not exert a substantial influence on the value of the firm. The Quick Ratio (QR), which measures the liquidity ratio, has a significant influence on the value of a company. Based on the F test, it can be inferred that both Return on Equity (ROE) and Quick Ratio have a statistically significant influence on the value of a corporation.